2022
DOI: 10.3390/ma15062027
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Excitation and Suppression of a Composite Laminate Plate Using Piezoelectric Actuators

Abstract: Piezoelectric (PZT) actuators bonded on a structure can be used to generate deformation and excite vibration for the shape control and vibration suppression, respectively. This article proposes a theoretical model for predicting vibrational response of a composite laminate plate with PZT actuators. The bending moment induced by the PZT actuator was obtained and applied on the composite laminate plate. Utilizing composite mechanics and plate theory, an analytical solution of the vibrational response of a compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…In recent investigations, researchers have also explored using PZT materials adhesively bonded to structures in various applications such as vibration, noise, and actual control of columns, beams, thin plates, etc. For instance, composite patches [ 31 ] have assessed vibration excitation and separation in laminates. At the same time, concrete beams have been used for damage evaluation in reinforced concrete structures with lap splices of tensional steel bars [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent investigations, researchers have also explored using PZT materials adhesively bonded to structures in various applications such as vibration, noise, and actual control of columns, beams, thin plates, etc. For instance, composite patches [ 31 ] have assessed vibration excitation and separation in laminates. At the same time, concrete beams have been used for damage evaluation in reinforced concrete structures with lap splices of tensional steel bars [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the LQR control algorithm was used to generate control voltages. Furthermore, multiple PZT actuators were employed to suppress the vibration of the composite laminate plate by Her [31].…”
Section: Introductionmentioning
confidence: 99%
“…Case studies of damage detection of the model bridge and real bridge structures employing Digital twin (DT) technology or DL algorithms, with high accuracy of 92 percent, are used to show the viability of the suggested framework [25]. In the latest studies, piezoelectric materials adhesively bonded to structures were also found in some other cases such as in composite patches [26] which is used to evaluate the vibration excitation and separation in laminates and concrete beams which is used for damage evaluation of reinforced concrete structures at lap splices of tensional steel bars [27]. Additionally, the performance of PZT actuators was found in the effects of a viscoelastic bonding layer bonded to an elastic structure [28].…”
Section: Introductionmentioning
confidence: 99%